A curricularização da extensão universitária frente aos marcos legais no contexto de um instituto federal de educação - Ferreira, Fernanda Emanuela (2020)
The publication of the National Education Plan (2014-2024), according to the law no. 13.0005/2014, brought the important challenge to higher education institutions in face of the need to review the curriculum of higher education courses to meet goal 12, strategy 12.7. This strategy indicates the mandatory inclusion of at least 10% of the total workload of the course reverted into programs or projects of university extension, oriented to areas of great social relevance. In the curricularisation process of higher education courses, the institution has the need to review its processes, train the academic community and verify the legal and institutional frameworks that guide the university extension action and its curricularisation in higher education courses. This study proposes the analysis of the extension curriculum scenario at the Federal Institute of Education, Science and Technology of Santa Catarina, considering the legal frameworks that guide the management of university extension. The methodological design brings a case study, qualitative approach, applied nature and descriptive objectives. To obtain results, primary data were used through semi-structured interviews and secondary data through documental analysis and bibliography pertinent to the subject. The results of the research indicate that the IFSC presents the alignment to the federal legal frameworks as far as curricularisation is concerned, but indicate that there is a need for recognition of the IFSC by society through extension and also the need to root the principles of extension in the organizational culture and to break prejudices in relation to extension actions, valued at the same time as teaching and research. The study demonstrates that the IFSC needs to review the instrument of evaluation of extension actions in order to assess the social impact generated by the institution in its surroundings, as well as the need to plan these actions according to the demand of society. The result is that there is a need to publicize the IFSC's extension actions that reach the internal and external community, the increase of the budget coming from partnerships, the engagement of the employees and the customization of the system that manages the extension in the institution. The adequacy to the processes that support the extension curriculum is necessary so that the IFSC can attend to the federal legal framework in effect until 2024, the term of the National Education Plan.